SOCRATES' ANAMNESIS OF THE CHILD'S UNCONSCIOUS MEMORY TO NATURE AND ROUSSEAU'S HUMAN DEVELOPMENT IN WORDSWORTH'S POEMS - admin admin; Rohmy Husniah (DIDAKTIKA, 2012)
Childhood experience toward nature is important in shaping one's development of understanding life therefore this research is conducted. The purposes of this research are to describe how the anamnesis arouse the speaker's mind to recollect his childhood memory in “The Intimations Ode” and “My Heart Leaps up when I Behold” and to describe the way the speaker sees the nature from his childhood memory to his adult in those two poems. The scope of the study is two of Wordsworth poems analyzed by using the theory of anamnesis stated by Socrates and the theory of human development stated by Rousseau. Anamnesis is a form of remembrance enabling man to perceive certain permanent, even eternal, truths once he remembers to remember them, and through their recollection raise them once again to conscious significance. Rousseau states the human's development in five stages of life; infancy, the age of nature, pre-adolescence, puberty, and adulthood. These two theories are applied because content of the two poems are about recollecting the speaker childhood experience (anamnesis) and about growing (human's development). The limitations of the study are the data are taken from two of Wordsworth poems and only the stanza(s) which have natural terms according to Wordsworth are analyzed. The methodology of the research is as follows: after doing the close reading, the poems are classified based on Wordsworth's natural terms, then paraphrasing, interpreting the poems based on the two theories by Socrates and Rousseau, and the last is concluding the result. The findings show that the speaker of the poem thrills and understands life by activating his imagery and recollecting the experience with nature, it means that the speaker does anamnesis to find the truth. The phases of life in “The Intimations Ode” are in lines with Rousseau's theory those are from the age of nature until adulthood; whereas in “My Heart Leaps Up When I Behold” the speaker's life of stages begins from the age of nature until he becomes old, the old age is not stated in Rousseau's theory. As the conclusion, anamnesis brings the speaker into three phases of thinking; the loss of vision (the difference feeling of seeing the same nature between the speaker's childhood and adulthood), the nature of the loss (the reason why the loss happens), and the acceptance. Five stages of life of the narrator are commenced from the age of nature, pre-adolescence, puberty, adulthood, and old age. The old age is a stage creating by Wordsworth for Rousseau does not mention the old stage. Rousseau only stated one's life development until the age of twenty five. The suggestion is that the further researchers to analyze other poems of Wordsworth and the other romantic poets' works as most of their poems are also about nature.